2017
DOI: 10.18632/oncotarget.23089
|View full text |Cite
|
Sign up to set email alerts
|

C-MYC and BCL-2 mediate YAP-regulated tumorigenesis in OSCC

Abstract: Transcriptional co-activator Yes-associated protein (YAP) is a key oncogene in mammalian cells. The present understanding of YAP in oral squamous cells carcinoma (OSCC) remains unclear. The purpose of this study is to investigate the effects of YAP on proliferation and apoptosis in OSCC and the molecular mechanism. The results showed the expression level of YAP was higher in OSCC tissues than that in adjacent normal tissues. Knockdown of YAP in CAL27 cell lines prohibited cell proliferation while augmented apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 35 publications
8
46
0
Order By: Relevance
“…Bcl-2 was identified as a YAP downstream protein. 47 In our work, YAP depletion downregulated Bcl-2 protein expression as a similar effect as MEL treatment mediated. Notably, YAP overexpression partially restored cell viability and reduced cisplatin-induced apoptosis.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Bcl-2 was identified as a YAP downstream protein. 47 In our work, YAP depletion downregulated Bcl-2 protein expression as a similar effect as MEL treatment mediated. Notably, YAP overexpression partially restored cell viability and reduced cisplatin-induced apoptosis.…”
Section: Discussionsupporting
confidence: 72%
“…Overexpression of YAP was detected in several cancers 46 and enabled to aid cell cycle progression via inducing cyclin proteins' expression and inhibiting p21. 47,48 In the present study, YAP silencing caused a reduced expression of Bcl-2 and GLUT-3, while its overexpression counteracted the MEL suppressive properties on HCC cells, indicating that MEL inhibited HCC growth partly through its inhibiting effect on YAP.…”
Section: Discussionsupporting
confidence: 49%
“…Originally, verteporfin was defined as a clinical photosensitizer and is an inhibitor of the YAP‐TEAD interaction . In previous reports, verteporfin without light activation was reported to exhibit cytotoxicity while suppressing the YAP pathway at a concentration of approximately 2–20 μ m (10–100 times higher than the concentration used in the current study) . In the present study, siRNA‐mediated knockdown of YAP did not reduce the MMP in GSCs, whereas verteporfin led to a reduction in the YAP‐knocked down GSCs.…”
Section: Discussionsupporting
confidence: 38%
“…We therefore screened drugs in clinical use for their ability to reduce MMP as an indicator and identified verteporfin (VPF, trade name Visudyne ® ), a Food and Drug Administration‐approved photoactivating drug that is used clinically for macular degeneration, as a candidate drug for targeting the OXPHOS in GSCs . Indeed, it has been reported that VPF suppresses cell proliferation and induces cell death of various cancer cells including glioblastoma cells as its side effect so far, but there is no report in GSCs . The medical effect of verteporfin is photoactivation‐dependent .…”
Section: Resultsmentioning
confidence: 99%
“…Cyclin intracellular concentrations are regulated by mitogenic signals such as Ras/MAP kinases, as well as Phosphoinositide 3-kinase. In the bladder [36], Oral squamous [37], gastric [38] cancer cells nuclear YAP leads to the upregulation of Cyclin D1, promoting cell proliferation. In ovarian granulosa cells, cyclin D2 is induced and under the control of FSH signaling, via a cyclic-AMP-dependent pathway [39].…”
Section: Discussionmentioning
confidence: 99%